ARANA, Aitor. Zaraitzuko hiztegia: Nafarroako Gobernua. Hiria argit 2001, 405 or. - Mujika, Luis Maria (EGAN, 2021)
LUIS MARIA MUJIKA: ARANA, Aitor. Zaraitzuko hiztegia Nafarroako Gobernua. Hiria argit 2001, 405 or.